The prevalence of coronary risk factors among children, ages 11 to 13, in selected Western Cape schools - De Klerk, Danelle Ria (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScSportSc)--University of Stellenbosch, 2002.